Tindak Pidana Kelalaian Lalu Lintas Yang Menyebabkan Kematian Perspektif Hukum Positif Dan Hukum Pidana Islam - Balqiz Rafi' Banalfa Izdihaar (An-Nisa: Journal of Islamic Family Law, 2025)
Law enforcement against criminal acts of traffic negligence (culpa) that result in death often raises debates about the proportionality of the sanctions imposed. This article aims to analyze the application of law in traffic negligence cases based on Indonesian positive law and Islamic criminal law. The study focuses on Court Decision Number 49/Pid.Sus/2023/PN Kdl, in which the defendant was sentenced to one year of city detention, even though Article 310 paragraph (4) of Law Number 22 Year 2009 stipulates a prison sentence of up to six years. This research uses a normative juridical method with a qualitative approach, through analysis of legal documents and in-depth interviews with judges who handle cases. The results showed that the judge considered the special conditions of the defendant, such as pregnancy, dependents of children under five, sincere remorse, and good faith in providing compensation to the victim's family. In the perspective of Islamic criminal law, the act is classified as jarimah qatlu al-khata', which is subject to sanctions in the form of diyat and expiation if unable to pay. This finding shows that there is a difference in approach between positive law and Islamic law, and raises discourse about the gap between legal norms and people's sense of justice. Therefore, it is necessary to evaluate the punishment policy in traffic negligence cases to better reflect substantive justice.